2010
DOI: 10.1002/asl.270
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble forecasting using TIGGE for the July–September 2008 floods in the Upper Huai catchment: a case study

Abstract: We present a case study using the TIGGE database for flood warning in the Upper Huai catchment (ca. 30 672 km 2 ). TIGGE ensemble forecasts from 6 meteorological centres with 10-day lead time were extracted and disaggregated to drive the Xinanjiang model to forecast discharges for flood events in July-September 2008. The results demonstrated satisfactory flood forecasting skills with clear signals of floods up to 10 days in advance. The forecasts occasionally show discrepancies both in time and space. Forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…This was the same composition procedure adopted by He et al (2010) and is one of the suggestions of Park et al (2008a,b). With this assumption, it is expected that the ensemble with more members will have a great influence on the results, but the investigation about multiple ways of combining forecasts is beyond the scope of the present work, and so we adopted the same procedure already tested by the cited authors.…”
Section: Hindcasting Experiments Setupmentioning
confidence: 98%
“…This was the same composition procedure adopted by He et al (2010) and is one of the suggestions of Park et al (2008a,b). With this assumption, it is expected that the ensemble with more members will have a great influence on the results, but the investigation about multiple ways of combining forecasts is beyond the scope of the present work, and so we adopted the same procedure already tested by the cited authors.…”
Section: Hindcasting Experiments Setupmentioning
confidence: 98%
“…Most scores for dichotomous evaluation are based on contingency tables, which include four Peirce's skill score (PSS, Eq. 3) (Hanssen and Kuipers, 1965) has been calculated for each station, taking the 90th percentile as threshold values (i.e., the 90th percentile from the sorted observations and from the sorted simulated values to discriminate each corresponding data series). PSS = hits hits + misses − false alarms false alarms + correct negatives…”
Section: Evaluation Of the Hydrological Modelingmentioning
confidence: 99%
“…Several flood forecasting systems are based on observed river level, while future values are extrapolated through river routing models or by coupling observed rainfall fields into hydrological models. The extension of the forecast horizon beyond the response time of a river basin is enabled by the use of numerical weather predictions (NWPs) as input to hydrological-hydraulic models (e.g., He et al, 2010;Hopson and Webster, 2010;Paiva et al, 2012;Thiemig et al, 2010). Recent review articles by Cloke and Pappenberger (2009) and by Alfieri et al (2012a) showed the strong potential of using ensemble NWPs to further extend the forecasting horizon in early warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of (Goswami et al, 2007). When various models that produce EPS from different weather centres are aggregated, the probabilistic nature of the ensemble precipitation forecasts is better retained and accounted for (He et al, 2009(He et al, , 2010). An ensemble of weather forecasts can be used on catchment hydrology and provide improved early flood forecasting as some of the uncertainties can be quantified .…”
Section: Introductionmentioning
confidence: 99%